New Population of the Rare Dragonfly Ophiogomphus howei (Odonata: Gomphidae) in Southern Michigan, United States. Issue 5 (3rd November 2020) - Craves, Julie A; O'Brien, Darrin S; Marvin, David A
Abstract: Ophiogomphus howei Bromley is a rare North American dragonfly, given a global conservation rank of Vulnerable by NatureServe. This species inhabits localized stretches of a limited number of typically undisturbed, high-quality, forested rivers in two disjunct regions in North America. We describe a new population in between the known ranges from an impaired river in a largely urban watershed in southern Michigan, United States. We also report a previously overlooked specimen from a new location in Pennsylvania, United States, and provide current occurrence and conservation status of the species in North America.